Detecção da produção de slime por estafilococos coagulase-negativa isolados de cateter venoso central - Bernardi, Adilson A. C.; Pizzolitto, Elisabeth Loshchagin [UNESP]; Pizzolitto, Antonio Carlos [UNESP] (My University, 2007)
Slime production is an important virulence factor of coagulase-negative Staphylococcus spp., allowing them to attach to smooth surfaces of biomaterials, and it has been associated with infections of implanted medical devices. In the present study the production of slime capsules in 27 strains of coagulase-negative Staphylococcus was investigated by culture in Congo Red agar (77.7% positivity), spectrophotometric or microplate method (81.4% positivity) and scanning electron microscopy (88.9% positivity). The resistance of coagulase-negative strains of Staphylococcus to various antimicrobial agents was also determined by agar disk diffusion. The proportion of strains resistant to penicillin G, oxacillin, erythromycin, clindamycin and gentamicin among the slime-producing staphylococci was 88.9%, 70.4%, 81.5%, 66.7% and 59.2%, respectively; all of the coagulase-negative staphylococci were susceptible to vancomycin. The strains isolated from central venous catheters were identified by a conventional method and the API Staph system. The 27 coagulase-negative Staphylococcus strains were identified as: S. saprophyticus (3.7%), S. xylosus (7.4%), S. haemolyticus (14.8%), S. epidermidis (37.0%), S. warneri (14.8%), S. lugdunensis (7.4%), S. hominis (7.4%), S. schleiferi (3.7%) and S. chromogenes (3.7%). It can be concluded that in the most of the coagulase-negative Staphylococcus species there was an association between slime production, the nosocomial origin of the strains and reduced sensitivity to the antibiotics, suggesting a pathogenic potential in the hospital environment.

A produção de slime é um importante fator de virulência dos estafilococos coagulase-negativa, permitindo-lhes aderir sobre as superfícies lisas de biomateriais, e por isso, é associada aos processos de infecção de implantes. No presente estudo a produção de slime em 27 cepas de estafilococos coagulase-negativa foi investigada por cultura em ágar vermelho Congo (77,7% de positividade), método espectrofotométrico ou da microplaca (81,4% de positividade) e microscopia eletrônica de varredura (88,9% de positividade). Foi também avaliada a resistência de estafilococos coagulasenegativa a vários antimicrobianos usando a técnica do disco difusão. A porcentagem de resistência à penicilina G, oxacilina, eritromicina, clindamicina e gentamicina em estafilococos produtores de slime foi respectivamente de 88,9%; 70,4%; 81,5%; 66,7% e 59,2%; todos os estafilococos coagulase-negativa foram vancomicina sensíveis. As cepas isoladas de cateter venoso central foram identificadas por método convencional e sistema API Staph. Os 27 estafilococos coagulase-negativa foram identificados como: S. saprophyticus (3,7%), S. xylosus (7,4%), S. haemolyticus (14,8%), S. epidermidis (37,0%), S. warneri (14,8%), S. lugdunensis (7,4%), S. hominis (7,4%), S. schleiferi (3,7%) e S. chromogenes (3,7%). Pode-se concluir que entre a maioria das espécies Staphylococcus coagulase-negativa houve associação entre a produção de slime, origem nosocomial das cepas e reduzida sensibilidade aos antimicrobianos, sugerindo potencial patogênico no ambiente hospitalar. Palavras-chave: estafilococos coagulase-negativa; slime; fatores de virulência; polissacarídeo extracelular; biofilme; sensibilidade aos antimicrobianos.
Detection of slime production by coagulase-negative staphylococci isolated from central venous catheter
Keywords: Biofilm; Coagulase-negative staphylococci; Extracellular polysaccharide; Slime; Virulence factors; antiinfective agent; congo red; vancomycin; virulence factor; analytic method; bacterial strain; bacterium culture; bacterium isolation; central venous catheter; coagulase negative Staphylococcus; controlled study; disk diffusion; drug sensitivity; nonhuman; scanning electron microscopy; slime; Staphylococcus chromogenes; Staphylococcus epidermidis; Staphylococcus haemolyticus; Staphylococcus hominis; Staphylococcus lugdunensis; Staphylococcus saprophyticus; Staphylococcus schleiferi; staphylococcus warneri; Staphylococcus xylosus